Rimegepant as an acute treatment in a refractory migraine patient non-responder to two anti-CGRP monoclonal antibodies and triptans: Case report and pharmacological considerations - Andrea Burgalassi; Giulia Vigani; Alberto Boccalini; Francesco De Cesaris; Guido Mannaioni; Alberto Chiarugi; Pierangelo Geppetti; Luigi Francesco Iannone (SAGE Publishing, 2024)
Background: Small molecule receptor antagonists (gepants), or monoclonal antibodies (mAbs) against calcitonin gene-related peptide (CGRP) have recently become available for migraine prophylaxis and/or acute treatment. Considering their shared mechanisms of action, if the failure to an anti-CGRP(R) mAbs preclude the effectiveness of gepants or vice versa is still unknown. Herein, we report the first case of a patient with refractory migraine responsive to the acute use of rimegepant that previously failed two different anti-CGRP(R) mAbs and with no response to other acute treatments. Finally, we performed a literature review on the use of gepants in patients that failed other anti-CGRP and/or triptans. Case: A 56-year-old female with a long history of chronic migraine without aura, fulfilling the EHF definition for a diagnosis of refractory migraine. Overall, the patient treated five not-consecutive migraine attacks. All of them were treated according to the predefined criteria. The mean (±SD) NRS before rimegepant assumption was 7.8 ± 0.9, all attacks cause at least severe impairment at onset, and no rescue medications were used. Pain free at 2 hours was achieved in three out of five attacks (60.0%), with no recurrence of migraine in the following 24 hours. The patient reported also a sustained benefit the day after the drug assumption. The response pain free was achieved after a mean time of 13.3 ± 4.5 minutes considering only attacks successfully treated (three out of five attacks). No adverse events were reported. Conclusions: In conclusion, rimegepant for acute treatment may be a viable option in patients with partial or no response to triptans that failed preventive treatments targeting the CGRP pathway, regardless to ligand or receptor. The failure of anti-CGRP(R) mAbs does not necessarily preclude the use of gepants (acute and/or preventive), but further studies are urgently needed to provide evidence on the efficacy of these treatments in managing drug-resistant migraine and to identify novel treatments for patients.